Juegos recreativos en el mejoramiento del estado de ánimo en el adulto mayor del Centro de Salud "Brisas del Mar” - Ramón Sotamba, Diana Elizabeth; Quinde Herrera, Joselyn Mishelle (Machala: Universidad Técnica de Machala, 2024)
The present research project was directed towards recreational games in improving the mood in the elderly, where the purpose is to analyze the recreational games that promote the mood of the elderly at the Brisas Health Center. Mar. The information collected was argued from the quantitative approach, having a descriptive methodology to determine the circumstance that occurs at the Brisas del Mar Health Center with respect to identifying recreational games to improve the mood of older adults. and propose methodological guidelines for the practice of recreational games with these people. The methods that were taken into account in this research are analytical and synthetic, deductive and inductive, other auxiliary methods are bibliographic and composite. In the literary review, fundamental information was obtained from scientific articles, while in the field investigation, information was collected through the survey to subsequently argue and maintain the integrative proposal that is the cooperation of the Health Center as an object of research study. In relation to the population, one specialist and ten older adults were taken into account, which is why the sample included the entire population to carry out this field work. The instruments used were the survey and statistics based on the objects of study, where four dimensions were originated and consecutively the indicators that served as a guide for the structure and development of the instruments with the help of the Likert scale, allowing the reception of the attitudes and opinions of the people who participated in this field work. The present research project was directed towards recreational games in improving the mood in the elderly, where the purpose is to analyze the recreational games that promote the mood of the elderly at the Brisas Health Center. Mar. The information collected was argued from the quantitative approach, having a descriptive methodology to determine the circumstance that occurs at the Brisas del Mar Health Center with respect to identifying recreational games to improve the mood of older adults. and propose methodological guidelines for the practice of recreational games with these people. The methods that were taken into account in this research are analytical and synthetic, deductive and inductive, other auxiliary methods are bibliographic and composite. In the literary review, fundamental information was obtained from scientific articles, while in the field investigation, information was collected through the survey to subsequently argue and maintain the integrative proposal that is the cooperation of the Health Center as an object of research study. In relation to the population, one specialist and ten older adults were taken into account, which is why the sample included the entire population to carry out this field work. The instruments used were the survey and statistics based on the objects of study, where four dimensions were originated and consecutively the indicators that served as a guide for the structure and development of the instruments with the help of the Likert scale, allowing the reception of the attitudes and opinions of the people who participated in this field work. The present research project was directed towards recreational games in improving the mood in the elderly, where the purpose is to analyze the recreational games that promote the mood of the elderly at the Brisas Health Center. Mar. The information collected was argued from the quantitative approach, having a descriptive methodology to determine the circumstance that occurs at the Brisas del Mar Health Center with respect to identifying recreational games to improve the mood of older adults. and propose methodological guidelines for the practice of recreational games with these people. The methods that were taken into account in this research are analytical and synthetic, deductive and inductive, other auxiliary methods are bibliographic and composite. In the literary review, fundamental information was obtained from scientific articles, while in the field investigation, information was collected through the survey to subsequently argue and maintain the integrative proposal that is the cooperation of the Health Center as an object of research study. In relation to the population, one specialist and ten older adults were taken into account, which is why the sample included the entire population to carry out this field work. The instruments used were the survey and statistics based on the objects of study, where four dimensions were originated and consecutively the indicators that served as a guide for the structure and development of the instruments with the help of the Likert scale, allowing the reception of the attitudes and opinions of the people who participated in this field work. The present research project was directed towards recreational games in improving the mood in the elderly, where the purpose is to analyze the recreational games that promote the mood of the elderly at the Brisas Health Center. Mar. The information collected was argued from the quantitative approach, having a descriptive methodology to determine the circumstance that occurs at the Brisas del Mar Health Center with respect to identifying recreational games to improve the mood of older adults. and propose methodological guidelines for the practice of recreational games with these people. The methods that were taken into account in this research are analytical and synthetic, deductive and inductive, other auxiliary methods are bibliographic and composite. In the literary review, fundamental information was obtained from scientific articles, while in the field investigation, information was collected through the survey to subsequently argue and maintain the integrative proposal that is the cooperation of the Health Center as an object of research study. In relation to the population, one specialist and ten older adults were taken into account, which is why the sample included the entire population to carry out this field work. The instruments used were the survey and statistics based on the objects of study, where four dimensions were originated and consecutively the indicators that served as a guide for the structure and development of the instruments with the help of the Likert scale, allowing the reception of the attitudes and opinions of the people who participated in this field work.
El presente proyecto de investigación se dirigió hacia los juegos recreativos en el mejoramiento del estado de ánimo en el adulto mayor, donde tiene como propósito analizar los juegos recreativos que fomenten el estado de ánimo de las personas de la tercera edad del Centro de Salud Brisas del Mar. La información recopilada se argumentó a partir del enfoque cuantitativo, disponiendo de una metodología descriptiva para determinar la circunstancia que se presenta en el Centro de Salud Brisas del Mar en respecto a identificar los juegos recreativos para mejorar el estado de ánimo de los adultos mayores y plantear orientaciones metodológicas para la práctica de los juegos recreativos con estas personas. Los métodos que se tomaron en cuenta en esta investigación es el analítico y sintético, el deductivo e inductivo otros métodos como auxiliares, son el bibliográfico y compuesto. En la revisión literaria se alcanzó información fundamental a partir de artículos científicos, en tanto que en la indagación de campo se recopiló información a través de la encuesta para posteriormente argumentar y mantener la propuesta integradora que es la cooperación del Centro de Salud como objeto de estudio de investigación. En relación a la población se tomó en cuenta a un especialista y a diez adultos mayores, por eso la muestra fue a toda la población para realizar el desarrollo de este trabajo de campo. Los instrumentos utilizados fueron la encuesta y estadística en base a los objetos de estudio, donde se originaron cuatro dimensiones y consecutivamente los indicadores que sirvieron como guía para la estructura y elaboración de los instrumentos con ayuda de la escala de Likert, permitiendo la recepción de las actitudes y opiniones de las personas que participaron en este trabajo de campo.
Keywords: RECREACION; JUEGO; ADULTO MAYOR; ESTADO DE ANIMO